Integrated pharmacokinetics and pharmacodynamics of Ro 48–8684, a new benzodiazepine, in comparison with midazolam during first administration to healthy male subjects - Van Gerven, J. M. A.; Roncari, G.; Schoemaker, R. C.; Massarella, J.; Keesmaat, P.; Kooyman, H.; Heizmann, P.; Zell, M.; Cohen, A. F.; Dingemanse, J. (British journal of clinical pharmacology, 1997)
Aims This study aimed to investigate the pharmacodynamics and pharmacokinetics of ascending doses of Ro 48–8684, compared with midazolam, in healthy subjects during first administration to man. Methods The study was double‐blind and five‐way crossover (three ascending doses, placebo, fixed midazolam dose), performed in two groups of five males. Ro 48–8684 was infused in doses of 0.1–0.3–1 mg in the first group, and 1–3–10 mg in the second, with different infusion rates (expressed as mg min−1 ) among doses. Midazolam was infused at 0.1 mg−1 kg. Infusions were stopped after 20 min or if sedation became too strong for proper performance of saccadic eye movements. Pharmacokinetics and pharmacodynamics and their relationships were evaluated as described in the companion article. Results Ro 48–8684 caused dose‐dependent sedation. No serious adverse events occurred. The volume of distribution and clearance of Ro 48–8684 were larger than of midazolam (337±114 vs 50±12 l and 2.4±0.5 vs 0.47±0.11 l min−1, resp). The recovery of saccadic eye movements from equal levels of sedation was on average almost half an hour faster for Ro 48–8684 than for midazolam, with considerable interindividual differences (range 2, 55 min). The doses of Ro 48–8684 leading to the same clinical endpoint as midazolam were comparable, but the corresponding predicted effect compartment concentrations of Ro 48–8684 were on average 2.6 times lower (range 1.5, 4.9 times). The slope of the linear concentration–effect‐relationship for saccadic peak velocity was on average 2.2 times steeper for 10 mg Ro 48–8684 than for midazolam (range 1.3, 3.3). The slope decreased on average 4.4‐fold (range 1.6, 7.3 times), with doses of Ro 48–8684 increasing from 1 to 10 mg. The metabolite Ro 61–2466 had a longer half‐life than the parent compound Ro 48–8684. The influence of this metabolite during prolonged administration should be further investigated. Conclusions These results show that Ro 48–8684 has a considerably shorter duration of action than midazolam. There may be a reduction of sensitivity to Ro 48–8684 with repeated administration of rising doses due to as yet undetermined factors.